SIDE EFFECTS CORRECTION IN COMBINED LIPID-CORRECTING THERAPY WITH STATINS AND FIBRATES USING LOW-MINERALIZED MINERAL WATER - Золотарьова, Н.А.; Solomko, O.V. (World of Medicine and Biology, 2020)
The side effects of the combination of statins and fibrates in patients with stable angina and low-mineralized silicon hydrocarbonate calcium-magnesium mineral water in their correction were studied. 64 patients were examined, divided into 2 groups. The first group received atorvastatin (10 mg) and fenofibrate (145 mg), the second group received low-mineralized silicon hydrocarbonate calcium-magnesium mineral water. It was found that use of atorvastatin and fenofibrate does not cause serious side effects, but undesirable effects, levels of alanine aminotransferase and creatine phosphokinase, increase. The positive effect of low-mineralized mineral water on clinical (prevention of symptoms from the digestive and hepatobiliary systems) and biochemical parameters were shown. Levels of creatine phosphokinase, alanine aminotransferase and aspartate aminotransferase decreased, significantly differing from group I (p
Keywords: side effects; statins; fibrates; mineral water; stable angina